Adsorption of Phenol from Aqueous Solution using Paper Waste - Adil Sabbar, Huda (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The exploitation of obsolete recyclable resources including paper waste has the advantages of saving resources and environment protection. This study has been conducted to study utilizing paper waste to adsorb phenol which is one of the harmful organic compound byproducts deposited in the environment. The influence of different agitation methods, pH of the solution (3-11), initial phenol concentration (30-120ppm), adsorbent dose (0.5-2.5 g) and contact time (30-150 min) were studied. The highest phenol removal efficiency obtained was 86% with an adsorption capacity of 5.1 mg /g at optimization conditions (pH of 9, initial phenol concentration of 30 mg/L, an adsorbent dose of 2 g and contact time of 120min and at room temperature). The well-known Langmuir and Freundlich adsorption models were studied. The results show that the equilibrium data fitted to the Freundlich model with R2=0.9897 within the concentration range studied. The main objective of this study is finding the best mixing and conditions for phenol removal by adsorption via paper waste.